Industrial symbiosis in Tanzania: A case study from the sugar industry - Rweyendela, Amani G.; Mwegoha, William J. S. (Taylor & Francis Online, 2024)
A research paper submitted to African Journal of Science, Technology, Innovation and Development Volume 13, 2021 - Issue 5, pages 595-606